2021
DOI: 10.3390/pathogens10070818
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulatory Effects upon Oral Application of Cumin-Essential-Oil to Mice Suffering from Acute Campylobacteriosis

Abstract: Human campylobacteriosis, commonly caused by Campylobacter jejuni, is a food-borne infection with rising prevalence causing significant health and socioeconomic burdens worldwide. Given the threat from emerging antimicrobial resistances, the treatment of infectious diseases with antibiotics-independent natural compounds is utmost appreciated. Since the health-beneficial effects of cumin-essential-oil (EO) have been known for centuries, its potential anti-pathogenic and immune-modulatory effects during acute ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Most important was the finding that the immunosuppressive drug rapamycin prevented campylobacteriosis in these mice and supported clearing of the pathogen [ 166 ], which provided the first experimental proof that the dampening of inflammation is a valuable target for prevention and treatment of C. jejuni infection. Furthermore, preclinical placebo-controlled intervention studies on SAB IL-10-deficient mice revealed that defined vitamins, including ascorbate [ 168 ] and vitamin D [ 73 , 169 ], the short chain fatty acid butyrate [ 170 ] and plant-derived compounds that have been used for an extensive period of time in traditional medicine, such as essential oils [ 171 , 172 , 173 , 174 ], curcumin [ 74 ], resveratrol [ 175 ], carvacrol [ 176 ], urolithin-A [ 177 ] and activated charcoal [ 178 ], effectively dampened inflammation in the course of murine campylobacteriosis. Their respective mechanisms of action demonstrate that (i) LOS activity, (ii) pro-inflammatory mediators including oxygen radicals, (iii) intestinal barrier function and (iv) C. jejuni -related pathogenicity factors are well suited as molecular targets for the treatment and prevention of campylobacteriosis [ 157 , 179 , 180 ].…”
Section: Anti-microbial and Anti-inflammatory Therapy Of Campylobacte...mentioning
confidence: 99%
“…Most important was the finding that the immunosuppressive drug rapamycin prevented campylobacteriosis in these mice and supported clearing of the pathogen [ 166 ], which provided the first experimental proof that the dampening of inflammation is a valuable target for prevention and treatment of C. jejuni infection. Furthermore, preclinical placebo-controlled intervention studies on SAB IL-10-deficient mice revealed that defined vitamins, including ascorbate [ 168 ] and vitamin D [ 73 , 169 ], the short chain fatty acid butyrate [ 170 ] and plant-derived compounds that have been used for an extensive period of time in traditional medicine, such as essential oils [ 171 , 172 , 173 , 174 ], curcumin [ 74 ], resveratrol [ 175 ], carvacrol [ 176 ], urolithin-A [ 177 ] and activated charcoal [ 178 ], effectively dampened inflammation in the course of murine campylobacteriosis. Their respective mechanisms of action demonstrate that (i) LOS activity, (ii) pro-inflammatory mediators including oxygen radicals, (iii) intestinal barrier function and (iv) C. jejuni -related pathogenicity factors are well suited as molecular targets for the treatment and prevention of campylobacteriosis [ 157 , 179 , 180 ].…”
Section: Anti-microbial and Anti-inflammatory Therapy Of Campylobacte...mentioning
confidence: 99%
“…The depletion of the murine gut microbiota by antibiotic pretreatment facilitated establishment of the enteropathogens alongside the gastrointestinal tract, whereas the il-10 gene knockout rendered mice susceptible to bacterial LOS resulting in clinical signs and immune-pathological responses upon oral C. jejuni infection as seen in human campylobacteriosis ( Mousavi et al, 2020a ). This C. jejuni infection and inflammation model has already been validated on numerous compounds, such as vitamins ( Mousavi et al, 2020b ; Lobo de Sá et al, 2021a ), plant derived biomolecules ( Mousavi et al, 2020c , d ), essential oils ( Bereswill et al, 2021a ; Heimesaat et al, 2021 ; Mousavi et al, 2021 ), activated charcoal ( Bereswill et al, 2021b ) as well as the short chain fatty acid butyrate ( Du et al, 2022 ), in order to assess their anti-microbial and immunomodulatory properties in acute campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous preclinical placebo-controlled intervention studies provided evidence for anti-pathogenic and immune-modulatory properties of several EOs derived from clove ( Bereswill et al, 2021 ), garlic ( Heimesaat et al, 2021b ), cardamom ( Heimesaat et al, 2021a ), and cumin ( Mousavi et al, 2021 ) in an acute murine campylobacteriosis model applying secondary abiotic (SAB) IL-10 deficient (IL-10 −/− ) mice. The secondary depletion of the commensal murine gut microbiota by antibiotic pretreatment and the lack of the anti-inflammatory il-10 gene are pivotal prerequisites for successful colonization of C. jejuni alongside the murine gastrointestinal tract and for the pathogen-induced pro-inflammatory immune responses mounting in acute enterocolitis ( Bereswill et al, 2011 ; Haag et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%